A Multistage Cooperative Nanoplatform Enables Intracellular Co‐Delivery of Proteins and Chemotherapeutics for Cancer Therapy. Issue 46 (9th October 2020) - Zhang, Peng; Zhang, Yu; Ding, Xiaoya; Shen, Wei; Li, Mingqian; Wagner, Ernst; Xiao, Chunsheng; Chen, Xuesi
Abstract: Combining intracellularly active proteins with chemotherapeutics represents a promising strategy for synergistic cancer therapy. However, the lack of nanocarrier systems for delivery into cancer cells and controlled intracellular release of both physicochemically very distinct cargos significantly impedes the biomedical translation of this combination strategy in cancer therapy. Here, a well‐designed triblock copolymer, mPEG‐ b ‐PGCA‐ b ‐PGTA, is reported for application in a multistage cooperative drug delivery nanoplatform that accomplishes effective intracellular co‐delivery of hydrophilic ribonuclease A (RNase A) and hydrophobic doxorubicin (DOX). RNase A bioreversibly modified with phenylboronic acid groups via a ROS‐cleavable carbamate linker is incorporated into the triblock copolymer nanoparticles with high efficiency through a pH‐reversible phenylboronic acid–catechol linkage. The reversible covalent conjugations between RNase A and the triblock copolymer endow the nanoparticles with high stability under normal physiological conditions. Upon cellular internalization, the cooperative release of DOX and RNase A from the triblock copolymer nanoparticles is triggered at multiple stages by endosomal acidic environment and subsequent DOX‐enhanced intracellular ROS environment. This leads to enhanced synergistic anticancer effects as demonstrated both in vitro and in vivo. Given the versatility of dynamic covalent conjugations, this work provides a universal and stable platform for intracellular co‐delivery of various combinations of proteins and chemotherapeutics. Abstract : A multistage cooperative drug delivery nanoplatform is developed to concurrently load doxorubicin and phenylboronic‐acid‐modified RNase A through hydrophobic interactions and dynamic covalent conjugation, respectively. This nanoplatform efficiently delivers both cargos into tumor sites with high systemic stability and mediates low‐pH‐ and ROS‐triggered cooperative release of doxorubicin and RNase A within tumor cells, leading to enhanced combined anticancer efficacy.